A randomized trial of low-dose ketamine and lignocaine infiltration for laparo-caecectomy in layer chickens (2012)
This study compared the anaesthetic effects of intramuscular injection of Ketamine (K) (15 mg/kg) with intramuscular injection of Ketamine (K) (15 mg/kg) and Lignocaine (L) (4 mg/kg) infiltration for laparocaecectomy in 12 layer chickens (1.1±0.06 Kg) randomized into two groups (K, 5 chickens and K- L, 7 chickens). The duration of recumbency of the K-L group (100.3±16.4 min) was significantly longer (p<0.05) than that of K group (33.8±6.0 min). Time to stand for the K-L group (20.8±4.0 min) was also significantly longer (p<0.05) than those of K group (10±1.4 min). The mean heart rates, respiratory rates and cloacal temperatures were lower in the K-L group than the K group. All the birds recovered smoothly and no mortality was recorded following the procedure. In the absence of inhalatory anaesthesia, low dose ketamine and lignocaine infiltration may be a preferred anaesthetic protocol for non-protracted abdominal procedures such as laparo-caecectomy in birds